2023
DOI: 10.1021/acs.langmuir.3c00010
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Nanostructure and Interactions in Water-in-Xylene Microemulsions Using Small-Angle X-ray and Neutron Scattering

Abstract: The ability to modulate the size, the nanostructure, and the macroscopic properties of water-in-oil microemulsions is useful for a variety of technological scenarios. To date, diverse structures of water-in-alkane microemulsions stabilized by sodium bis(2-ethylhexyl) sulfosuccinate (AOT) have been extensively studied. Even though the decisive parameter which dictates the phase behavior of micremulsions is the nature of the continuous phase, relatively very few reports are available on the structure and interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 85 publications
(214 reference statements)
0
4
0
Order By: Relevance
“…86,88 Our previous investigation shows that when dodecane is replaced with p -xylene, the water-in-xylene RMs prepared at similar conditions ( ω = 10 and Φ = 0.005 to 0.20) are found to consist of AOT stabilized water drops that are spherical in shape. 90 Contrary to the case of D 2 O-in-dodecane RMs, the size of spherical D 2 O droplets remains almost constant and the attractive interactions become more pronounced when Φ is increased. Moreover, when RMs containing D 2 O-in-xylene prepared at fixed Φ are subjected to different temperatures ( T ) ranging from 20 °C to 50 °C, only a marginal decrease in the size was observed, whereas the inter-droplet interactions remain almost unchanged.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…86,88 Our previous investigation shows that when dodecane is replaced with p -xylene, the water-in-xylene RMs prepared at similar conditions ( ω = 10 and Φ = 0.005 to 0.20) are found to consist of AOT stabilized water drops that are spherical in shape. 90 Contrary to the case of D 2 O-in-dodecane RMs, the size of spherical D 2 O droplets remains almost constant and the attractive interactions become more pronounced when Φ is increased. Moreover, when RMs containing D 2 O-in-xylene prepared at fixed Φ are subjected to different temperatures ( T ) ranging from 20 °C to 50 °C, only a marginal decrease in the size was observed, whereas the inter-droplet interactions remain almost unchanged.…”
Section: Resultsmentioning
confidence: 84%
“…6 shows the probability density distribution functions (PDDF) p ( r ) vs. r obtained from SAXS analysis on the D 2 O-in-oil RMs where the continuous (oil) phase is (i) p -xylene (ii) dodecane, and (iii) a mixture of p -xylene and dodecane in the ratio of 1 : 9 by volume when the volume faction of dispersed phase, Φ = 0.005, see Section 2.2 for more details on the procedure. The p ( r ) vs. r for p -xylene/D 2 O/AOT RM at ω = 10 and Φ = 0.005 from our previous investigation 90 is included to draw a comparison of the nanostructure of the RMs when different oils are used. It is observed that the p ( r ) vs. r of p -xylene/D 2 O/AOT RM is a bell shaped curve, depicting spherical droplets whereas for dodecane/D 2 O/AOT system, a peak followed by a long tail is observed, pointing to the presence of elongated droplets (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The onset of structuring, as derived from the extrapolation limit of the scattered intensity at zero angle, I(0), corresponds to the transition seen in conductivity. Detailed study of the zero angle in scattering and its relation with chain interdigitation has been made by Rastogi and co-workers using xylene [41]. As we see in the supplementary material, the dismutation regime dominates when no water cores are present and dismutation becomes energetically favourable.…”
Section: Observation Of Conductivity Variation Obtained By Dilution W...mentioning
confidence: 94%
“…Since no other study and only five data points are available, it is not possible at the present stage to confirm this observation. A more detailed study linking conductivity measured to carefully established scattering has become available recently [41]. This work was focused on xylene, a polar solvent in which all ternary phase equilibria have been determined: AOT and xylene are fully miscible even in the absence of water and show a large domain of reverse hexagonal phases [12].…”
Section: Comparison With Earlier Observationsmentioning
confidence: 99%